Students' Perception on Healthy Sleep Education for Insomnia Risk Reduction in Adolescents - Tisa Amalia; Elsa Marliana; Ayu Izzatin Haifa; Nindya Sekar Mayuri; Fathimatuzzahroh; Ghina Rifa Cahyani; Maria Aditya; M. Pasha Aditya; Shilfa Zahratunnisa; Fachri Alim Lukmanul Hakim; Pertiwi Azzahra Fauzi (Kirana Publisher (KNPub), 2026)
The rapid development of digital technology has transformed adolescent behavioral patterns, particularly in social media usage, leading to increased insomnia risk. This community service activity aimed to evaluate the effectiveness of healthy sleep pattern education in reducing insomnia risk among adolescents in Sukatani area. A pre-experimental design with one-group pre-test and post-test was employed involving 30 adolescents aged 15-18 years. The educational intervention was conducted through interactive counseling sessions supported by presentation media at Sukatani Public Health Center on May 23, 2026. Knowledge assessment was performed using a validated questionnaire consisting of 8 multiple-choice and true/false questions. Data were analyzed using descriptive statistics and paired t-test. Results showed that the mean pre-test score was 95.8, which increased to 97.5 in the post-test, with an average increase of 1.7 points. The paired t-test analysis revealed a significant improvement in knowledge scores (p<0.05). However, only 20% of participants showed individual score improvement due to ceiling effect, where 73.3% of participants had already achieved perfect scores in the pre-test. The educational program effectively improved adolescents' knowledge about healthy sleep patterns and insomnia prevention. Interactive educational methods are recommended for adolescent health education programs, with consideration of baseline knowledge levels in program evaluation design